A numerical study on the radiative heat transfer aspects of hybrid nanofluid flow past a deformable rotating cone - Kumar, K. Thanesh; Remidi, Srinivas; Nagapavani, M.; Prasad, Koushik V.; Karthik, K.; Kumar, Raman; Naveen Kumar, R. (Multiscale and Multidisciplinary Modeling, Experiments and Design, 2024)
The flow of hybrid nanoliquid produced by the stretching or shrinking rotating cone under the wall-deforming boundary conditions is studied in the present article. The effect of homogeneous-heterogeneous chemical reactions and thermal radiation on the stream is also considered in the modelling to discuss mass and heat transport. Engineers and scientists may advance the efficacy of chemical reactions or heat transmission by designing systems with optimal flow and researching how reactions affect the flow. The modelled governing partial differential equations (PDEs) are converted to ordinary differential equations (ODEs) with similarity variables. The obtained ODEs are solved numerically by employing Runge Kutta Fehlberg’s fourth-fifth order (RKF-45) scheme. The consequence of several dimensionless variables on the numerous profiles is portrayed with graphical representations. The impact of the ratio of deformation to rotation parameter on the behaviour of fluid velocity profiles is illustrated. Results expose that the improvement in radiation parameter upsurges the thermal profile. The intensification in the deformation to rotation parameter ratio declines the temperature. The concentration declines as the values of homogeneous and heterogeneous parameters increases.